The risk of inbreeding versus outbreeding depression in managing an endangered and locally adapted population of a sedentary bird - Grace Walsh; Barry J. McMahon; Filip Thörn; Patrik Rödin‐Mörch; Martin Irestedt; Jacob Höglund (Conservation Science and Practice)
Abstract A debate in conservation genomics centers on whether to conserve small, fragmented populations independently or blend them through translocations from larger populations. Translocations of red grouse (Lagopus scotica) from Great Britain to supplement the Irish population have been suggested. We incorporate a variety of genetic datasets to address this. We used genome wide data from 23 contemporary and historic red grouse from Great Britain and Ireland. We also investigate microsatellite data, sequence candidate pigmentation genes, and assess phenotypic color variation. Genomic data indicate higher inbreeding in Irish grouse relative to an English population and significant divergence for genomic (FST = 0.095) and microsatellite (FST = 0.03) markers. Contemporary Ne was seven times smaller in the Irish population compared to the English. We identified divergent regions linked to pigmentation, immune response, and food intake. We show phenotypic differences in plumage color and sequence divergence among coding regions in the melanin pathway including MC1R (FST from genomic data of 0.3). The two populations thus appear locally adapted and this divergence between the source and target population when used for conservation translocations can swamp locally adapted alleles and/or introduce maladapted genotypes, leading to outbreeding depression. While it is important to avoid inbreeding by sustaining larger populations, our research emphasizes the need for practitioners to consider population divergence and local adaptation. We advocate against translocations between Ireland and Britain as a conservation strategy in this particular case and underscore the importance of prioritizing local populations where possible.